PERSPEKTIF TEORITIS PENDEKATAN SISTEM DALAM MANAJEMEN PENDIDIKAN ISLAM - Faradilla Andini; Intan Permata Hati; Romlah; Zainal Arifin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The systems approach in Islamic education management is a holistic frameworkdesigned to optimize educational components in an integrated manner to achieveIslamic educational goals. This study addresses the lack of understanding of thesystems approach, challenges in its implementation, and the need forcomprehensive evaluation in Islamic education management. The objective is todescribe the concept of the systems approach, the interaction among itscomponents, and the challenges and solutions for its application. The researchmethodology is descriptive qualitative, utilizing theoretical analysis of relevantliterature, including primary sources such as the Qur'an, Sunnah, and ijma’ ulama.The findings reveal that the systems approach effectively integrates curriculum,educators, students, infrastructure, and community support in managing education.Key challenges identified include resistance to change, resource limitations, andinconsistent performance measurement. Proposed solutions include training,integrated management systems, and the development of performance indicators.The study concludes that the systems approach can enhance the quality of Islamiceducation by fostering synergy among components and promoting Islamic values,ultimately producing academically excellent and morally upright generations.